Впровадження енергоефективних технологій при будівництві нової комерційної нерухомості в Україні - Бахтін, Дмитро; Bakhtin, Dmytro (Видавництво Львівської політехніки, 2020)
В статті визначені основні умови та проблеми впровадження енергоефективних технологій для бізнесу в Україні та розглянутий проектний досвід будівництва “зелених” комерційних будівель, які були зведені в останні роки.

The article identifies the main conditions and problems of introducing energy-efficient technologies for business in Ukraine and considers the design experience of building green commercial buildings that have been erected in recent years (innovative parks UNIT.City in Kiev and LvivTech.City in Lviv, on the Sobachie mouth peninsula, Astarta Business Center in Kiev, etc.) It has been established that the main problem of introducing energy-efficient technologies in public commercial projects is the insufficient participation of the state in financing and stimulating business. To establish this process, it is necessary to amend the legislation on land, on technology parks, on the procedure for taxation and subsidies to enterprises that develop energy-efficient technologies in construction at different levels. The features of Ukrainian development and the dependence of the profitability of the building on the quality of the architectural solution are considered. It has been found that energy-efficient technologies are of interest only to a small fraction of commercial real estate developers who are focused on the development of the IT industry. To be able to deploy economically feasible energy-efficient commercial projects in other sectors, both state support and business entry into foreign investment markets will need additional guarantees and reduce the risk of waiting for a 10–15-year payback period for large-scale innovative projects. It was revealed that the IT industry has become a catalyst for the development of innovations in the field of energy-efficient construction. Thanks to it, architects were able to realize energy-efficient public buildings of the commercial sector, which are the prototypes for further similar design in Ukraine and the basis for developing the principles of “green” construction, the main provisions of which can be reflected in the changes to the state building standards of Ukraine.
The introduction of energy-efficient technologies in the construction of a new commercial real estate in Ukraine
Keywords: енергоефективність; девелопмент; громадські будівлі; сталий розвиток; інноваційний парк; рентабельність; energy efficiency; development; public buildings; sustainable development; innovation park; profitability; 725; 697.1